Combination of sugar and stable isotopes analyses to detect the use of nongrape sugars in balsamic vinegar must. (30th July 2018) - Perini, Matteo; Nardin, Tiziana; Camin, Federica; Malacarne, Mario; Larcher, Roberto
Abstract: "Aceto Balsamico di Modena" (ABM) is a protected geographical indication salad dressing obtained from cooked and/or concentrated grape must, with the addition of wine vinegar and a maximum of 2% caramel (EU Reg 583/2009). In this study, we investigated whether the combination of 13 C/ 12 C of ethanol using isotope ratio mass spectrometry with 2 H‐site‐specific natural isotope fractionation–nuclear magnetic resonance and minor sugars using ion chromatography with pulse amperometric and charged aerosol detection is able to improve detection of sugar addition to ABM must. A large selection of authentic Italian grape musts and different samples of balsamic vinegar with an increasing percentage of added beet, cane, and sugar syrups were considered. The possible degradation of sugars in the ABM matrix during shelf life was also investigated. While stable isotope ratios analysis remains the favoured method for determining cane and beet sugar addition, dosage of minor sugar (in particular maltose) proved to be very useful for detecting the addition of sugar syrup. Thanks to this innovative approach, 3 out of 27 commercial ABMs were identified as adulterated. A combination of stable isotope ratio and ion chromatography with pulse amperometric and charged aerosol detection analysis can be therefore proposed as a suitable tool for detecting the authenticity of ABM must.